Improving Impulse Buying Through Store Environment: The Roles of Shopping Enjoyment and Money Availability - Nailul, Muhammad; Thoyib, Armanu; Wahdiatmoko (Jurnal Aplikasi Manajemen, 2025)
Impulsive buying behavior has become a fascinating area of study in consumer behavior, particularly in today's highly competitive retail landscape, where spontaneous purchases often play a pivotal role in driving sales. This study delves into how the store environment influences impulsive buying, both directly and indirectly, by examining the sense of shopping enjoyment it creates and the moderating role of money availability. Rooted in the Stimulus-Organism-Response (S-O-R) Model, Flow Theory, and existing insights on impulsive buying, this study adopts a quantitative approach through surveys. Feedback was gathered from 200 participants who frequent three popular clothing stores in Malang, capturing their authentic experiences and purchasing dynamics. Using purposive sampling, the study focuses on individuals whose shopping habits reflect the nuances of impulsive buying, aiming to uncover how emotional, environmental, and financial factors interplay to shape their decisions. The structural relationships between variables were analyzed using SmartPLS 3.0, revealing compelling insights into the consumer experience. The findings highlight that the store environment significantly enhances impulsive buying behavior, with shopping enjoyment as a partial bridge in this relationship. Moreover, the availability of money strengthens the connection between the store environment and impulsive buying, magnifying the impact of an engaging atmosphere on spontaneous purchase decisions. What sets this study apart is its exploration of shopping enjoyment as a fleeting emotion and a meaningful link in the consumer decision-making process, coupled with the pivotal role of money availability as a moderating factor. These insights provide actionable guidance for retailers to craft inviting and enjoyable store environments while being mindful of customers’ financial realities, which can create moments of delight that translate into increased sales. This approach underscores the power of understanding the human side of consumer behavior in shaping memorable shopping experiences.